HUBUNGAN KESEIMBANGAN, DAN KELENTUKAN DENGAN KEMAMPUAN SEPAK SILA PADA PERMAINAN SEPAKTAKRAW - Fahrizal, Fahrizal (UNIVERSITAS NEGERI MAKASSAR, 2019)
This study aims to obtain answers to the problems of the relationship of balance, and flexibility with the ability of sila in SMP Negeri 1 Sungguminasa, Gowa Regency. This research is descriptive of two independent variables and one dependent variable. The population and sample were students of SMP Negeri 1 Sungguminasa, Gowa Regency, selected by random sampling, a sample of 30 people was obtained. The data analysis technique used is single correlation analysis and multiple correlation using computer facilities through the SPSS program. Based on the results of data analysis, it can be concluded as follows: (1) There is a balance relationship with the ability of football in the State Junior High School 1 Sungguminasa, Gowa Regency, with a r count (ro) = 0.649 (P <0.05). (2) There is a relationship between flexibility and the ability to play soccer in SMP Negeri 1 Sungguminasa, Gowa Regency, with a r count (ro) = 0.578 (P <0.05). (3) There is a relationship of equilibrium, and flexibility with the ability to play football at the State Junior High School 1 in Sungguminasa, Gowa Regency, with a calculated R value (Ro) = 0.672 (P <0.05).